Aerospace titanium alloy cutting fluid and preparation method and application thereof
By using carbon quantum dot@titanium dioxide core-shell structure materials and a segmented cutting fluid recycling method in aerospace titanium alloy cutting fluid, the lubrication problem in the cutting process of aerospace titanium alloys has been solved, improving processing efficiency and environmental friendliness, and reducing costs.
Patent Information
- Application Number
- CN202410184018.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-19
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-02-19
AI Technical Summary
Existing technologies have failed to effectively solve the lubrication problem of aerospace titanium alloys during the cutting process. The differences in composition and function between traditional lubricating oils and cutting fluids make them incompatible. The application of carbon quantum dot@titanium dioxide core-shell structure materials in cutting fluids still needs improvement.
A cutting fluid for aerospace titanium alloys was prepared by using carbon quantum dot@titanium dioxide core-shell structure material as the main component, combined with wetting agents and rust inhibitors. The lubrication effect was optimized by recycling the cutting fluid in stages based on different cutting time periods.
It improves tool life during the machining of aerospace titanium alloys, reduces pollution from cold rolling emulsified oil, achieves environmentally friendly and efficient lubrication performance, and lowers costs.
Smart Images

Figure CN118028045B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aerospace titanium alloy technology, specifically to an aerospace titanium alloy cutting fluid, its preparation method, and its application. Background Technology
[0002] Although aerospace titanium alloys possess numerous superior properties, they are typically difficult to machine due to their high cutting temperatures, high chemical reactivity, low coefficient of deformation, low elastic modulus, and severe chilling. These characteristics make titanium machining extremely challenging, resulting in high tool consumption and low machining efficiency. Therefore, a good cutting fluid is needed for lubrication to mitigate these problems during titanium alloy machining.
[0003] Carbon quantum dots (CQDs) are novel derivatives of carbon, representing a class of zero-dimensional carbon nanomaterials with significant fluorescence properties. They consist of ultrafine, dispersed, quasi-spherical carbon nanoparticles with a size less than 10 nm. CQDs exhibit uniform particle size distribution, good water dispersion stability, ideal reactivity, and excellent mechanical properties, showing promising applications in many fields such as medical imaging, environmental monitoring, chemical analysis, catalyst preparation, and energy development. Our research has revealed that due to the high chemical inertness of carbon materials, CQDs possess high environmental stability. Furthermore, the numerous hydrophilic functional groups, such as carboxyl groups, on the surface of CQDs exhibit excellent solubility in water, enabling their application in metal cutting lubrication.
[0004] Nano-TiO2 is often used in lubrication processes due to its grinding and polishing properties, and it is also frequently used as the shell material for core-shell structures. Some existing technologies have also explored this area.
[0005] For example, patent CN111004665B discloses a method for preparing graphite-based nano-titanium dioxide lubricating oil. The method involves: a) pulverizing graphite into micro-powder with a particle size of 4-10 μm; b) adding potassium permanganate, sulfuric acid, nitric acid, and titanium tetrachloride to the micro-powdered graphite, reacting for 100-140 min, washing, filtering, drying, and then expanding at high temperature in a muffle furnace to obtain graphite-based nano-titanium dioxide expanded graphite; c) pulverizing again to a particle size of 1-4 μm; d) surface modification with oleic acid, followed by addition to the lubricating oil base oil, and ultrasonic homogenization at 30-50℃. This method uses physical and chemical methods to pulverize graphite to 1-4 μm, while simultaneously attaching titanium dioxide in nano-form to the micron-sized graphite matrix, forming a graphite-based nano-titanium dioxide composite material. This improves the pressure-reducing and anti-wear properties, self-healing properties, and stability of graphite in the lubricating oil.
[0006] Patent CN111363601B discloses a fluorinated graphene oxide / titanium dioxide nano-lubricant additive, its preparation method, and its application. Fluorinated graphene oxide, an acidic substance, and a water / ethanol solution are uniformly mixed to form a mixed solution. A titanium source is added for aging, followed by the addition of ethanol to obtain a uniformly mixed reaction system. This uniformly mixed reaction system is then subjected to a hydrothermal reaction at 160–190°C for 20–30 hours to obtain the fluorinated graphene oxide / titanium dioxide nano-lubricant additive. The obtained composite material exhibits good compatibility with lubricating oil, resulting in a uniformly dispersed lubricating oil. This modified lubricating oil demonstrates significantly better friction-reducing and anti-wear properties under different load conditions than pure lubricating oil. The required amount of nano-lubricant additive is very small, effectively saving resources. Furthermore, the preparation process is simple, economical, and practical, making it suitable for industrial application.
[0007] However, the aforementioned research has not solved the problems encountered in cutting aerospace titanium alloys. Firstly, lubricating oil and cutting fluid provide different lubrication methods, and their compositions and functions differ, making them incompatible. Secondly, the application of carbon quantum dot@titanium dioxide core-shell structure materials in cutting fluids requires further modifications to meet the cutting requirements of aerospace titanium alloys. No in-depth research has yet been conducted on this issue. Summary of the Invention
[0008] To address the aforementioned problems, this invention provides an aerospace titanium alloy cutting fluid, its preparation method, and its application.
[0009] The technical solution of this invention is: An aerospace titanium alloy cutting fluid, by weight percentage, comprises the following components: 0.5-1.5% carbon quantum dot@titanium dioxide core-shell structure material, 0.5% wetting agent, 1-2.5% rust inhibitor, and the balance being deionized water.
[0010] Furthermore, the wetting agent is sodium dodecylbenzenesulfonate, and the rust inhibitor is triethanolamine.
[0011] Note: Sodium dodecylbenzenesulfonate is used as a wetting agent to provide good lubrication assistance, and triethanolamine is used as a rust inhibitor to effectively prevent aerospace titanium alloys from rusting.
[0012] Furthermore, the preparation method of the carbon quantum dot@titanium dioxide core-shell structure material is as follows: S1. Preparation of carbon quantum dots: By weight, 1-3 parts of sucrose, chitosan, or glucose are placed in 30-50 parts of ethanol solution and ultrasonically treated in a cold water bath for 20-30 min. Then, 3-5 parts of 30% hydrogen peroxide solution are added to obtain the first mixture. The first mixture is then placed in a reaction vessel and heated to 120-200℃ for 12-24 h to obtain a precipitate. After centrifugation and washing, carbon quantum dots are obtained. S2. Preparation of carbon quantum dot@titanium dioxide core-shell structure: By weight, 1-5 parts of carbon quantum dots are dissolved in 30-50 parts of ethanol solution and stirred to obtain a second mixture. While stirring, acetic acid solution is added dropwise until the pH of the second mixture is 1.7. Finally, 12-20 parts of tetrabutyl titanate are added dropwise. After stirring and mixing at room temperature for 8-12 hours, a third mixture is obtained. After centrifuging and washing the third mixture, carbon quantum dot@titanium dioxide core-shell material is obtained.
[0013] Furthermore, in step S1, the temperature of the cold water bath is 2~6℃.
[0014] Note: Controlling the temperature of the cold water bath in step S1 allows sugars to dissolve stably and quickly in the ethanol solution.
[0015] Furthermore, the mass concentration of the ethanol solution in step S1 and the ethanol solution in step S2 is both 95%, and the mass concentration of the acetic acid solution in step S2 is 60-80%.
[0016] Note: Using ethanol and acetic acid solutions of appropriate concentrations makes the preparation process more stable and efficient.
[0017] Furthermore, the stirring speed in step S2 is 100~150 rpm, and the room temperature is 20~30℃.
[0018] Note: Choosing an appropriate stirring speed can promote the reaction.
[0019] Furthermore, in step S2, the carbon quantum dots used are 6nm±1nm in size, and the carbon quantum dot@titanium dioxide core-shell structure material prepared is 80~100nm in size.
[0020] This invention also provides a method for preparing an aerospace titanium alloy cutting fluid. The method involves adding carbon quantum dot@titanium dioxide core-shell structure material, a wetting agent, and a rust inhibitor to deionized water according to the specified ratio. After ultrasonic treatment for 20-30 minutes, the mixture is heated to 60-80°C and stirred for 20-30 minutes at a stirring speed of 200-300 rpm to obtain the aerospace titanium alloy cutting fluid.
[0021] The present invention also provides an application of an aerospace titanium alloy cutting fluid, which is applied to the cutting lubrication of aerospace titanium alloys based on the above-mentioned aerospace titanium alloy cutting fluid.
[0022] Furthermore, the application method is as follows: Each cutting of aerospace titanium alloy is divided into three stages according to the total cutting time: the first stage, the middle stage, and the last stage. The time ratio of the first stage, the middle stage, and the last stage is 3:3:4, and the cutting fluid used in each stage is different. In the initial stage, the cutting fluid used is the aerospace titanium alloy cutting fluid. After the aerospace titanium alloy cutting fluid is sprayed onto the titanium alloy cutting part for cooling and lubrication, the used aerospace titanium alloy cutting fluid is collected and filtered through a 0.05~0.1mm filter screen to obtain a first-use reusable cutting fluid. In the middle stage, the cutting fluid used is the primary recycled cutting fluid. The primary recycled cutting fluid is used again to cool and lubricate the cutting part of the aerospace titanium alloy by spraying. Then, the used primary recycled cutting fluid is collected and centrifuged at a speed of 5000~10000 rpm for 3~5 minutes to obtain secondary recycled cutting fluid. In the later stage, the cutting fluid used is a mixture of the secondary recycled cutting fluid and the aerospace titanium alloy cutting fluid in a volume ratio of 8:3. After the secondary recycled cutting fluid and the aerospace titanium alloy cutting fluid are mixed in a volume ratio of 8:3, the cutting part of the aerospace titanium alloy is cooled and lubricated again by spraying. The cutting fluid flow rate is the same when cutting aerospace titanium alloys in the front, middle and rear sections, which is 5~10L / min.
[0023] Explanation: By defining the specific application method of aerospace titanium alloy cutting fluid, it can be recycled according to the cutting time period during a single cutting operation. Different treatment methods are adopted for different recycled cutting fluids. The total cutting time required is determined based on the size of the aerospace titanium alloy parts, and then the cutting time period is divided according to the total time. The cutting fluid is adjusted in a targeted manner for each time period to ensure the lubrication effect, making the aerospace titanium alloy cutting process more efficient, reasonable and environmentally friendly, saving costs and avoiding waste.
[0024] The beneficial effects of this invention are: (1) The aerospace titanium alloy cutting fluid of the present invention uses carbon quantum dot@titanium dioxide core-shell structure material as the main raw material. It has the advantages of excellent dispersion performance, good stability, long-lasting lubrication performance and green environmental protection. It greatly improves the service life of various tools during the processing of aerospace titanium alloy, reduces the pollution caused by traditional cold rolling emulsified oil, and solves the problems of environmental pollution and harm to human body caused by traditional cutting fluid.
[0025] (2) The preparation method of the aerospace titanium alloy cutting fluid of the present invention is convenient, easy to implement, and can be mass-produced. The carbon quantum dot@titanium dioxide material obtained is nano-sized spherical particles with uniform particle size of about 80~100nm, which makes the aerospace titanium alloy cutting fluid have good lubrication performance.
[0026] (3) The application method of the aerospace titanium alloy cutting fluid of the present invention limits the specific application method of the aerospace titanium alloy cutting fluid so that it can be recycled according to the cutting time period during a single cutting. Different treatment methods are adopted for different recycled cutting fluids. The total cutting time required is determined according to the size of the aerospace titanium alloy parts, and the cutting time period is divided according to the total time. The cutting fluid is adjusted in a targeted manner for each time period to ensure the lubrication effect, making the aerospace titanium alloy cutting process more efficient, reasonable and environmentally friendly, saving costs and avoiding waste. Attached Figure Description
[0027] Figure 1 This is a transmission electron microscope image of the carbon quantum dots prepared in step S1 of Example 1 of the present invention; Figure 2 These are transmission electron microscope images and corresponding mapping diagrams of the carbon quantum dot@titanium dioxide core-shell material prepared in step S2 of Example 1 of this invention. Figure 3 This is a graph showing the friction coefficients of the aerospace titanium alloy cutting fluid prepared in Example 1 of the present invention under different loads; Figure 4 These are SEM images of wear marks on titanium alloys cut with four different cutting fluids in Experimental Example 2 of this invention; Figure 5 This is a flowchart of a method for preparing an aerospace titanium alloy cutting fluid according to the present invention. Detailed Implementation
[0028] Example 1 An aerospace titanium alloy cutting fluid, by weight percentage, comprises the following components: 1% carbon quantum dots@titanium dioxide core-shell structure material, 0.5% wetting agent, 1.5% rust inhibitor, and the balance being deionized water; the wetting agent is sodium dodecylbenzene sulfonate, and the rust inhibitor is triethanolamine.
[0029] The preparation method of carbon quantum dot@titanium dioxide core-shell structure material is as follows: S1. Preparation of carbon quantum dots: By weight, 2 parts of sucrose were placed in 40 parts of ethanol solution and ultrasonically treated in a cold water bath for 25 min at a temperature of 3°C. Then, 4 parts of 30% hydrogen peroxide solution were added to obtain the first mixture. The first mixture was then placed in a reaction vessel and heated to 160°C for 18 h to obtain a precipitate. The precipitate was centrifuged and washed to obtain carbon quantum dots. S2. Preparation of carbon quantum dot@titanium dioxide core-shell structure: By weight, 3 parts of carbon quantum dots were dissolved in 40 parts of ethanol solution and stirred to obtain a second mixture. The size of the carbon quantum dots used was 6nm±1nm. Acetic acid solution was added dropwise while stirring until the pH of the second mixture was 1.7 and the mass concentration of the acetic acid solution was 70%. Finally, 15 parts of tetrabutyl titanate were added dropwise. After stirring and mixing at room temperature for 10h, a third mixture was obtained. The stirring speed was 120rpm and the room temperature was 22℃. After centrifuging and washing the third mixture, carbon quantum dot@titanium dioxide core-shell material with a size of 80~100nm was obtained. In both steps S1 and S2, the mass concentration of the ethanol solution is 95%.
[0030] Example 2 The difference between this embodiment and Embodiment 1 is that: An aerospace titanium alloy cutting fluid, by weight percentage, comprises the following components: 0.5% carbon quantum dots@titanium dioxide core-shell structure material, 0.5% wetting agent, 1% rust inhibitor, and the balance being deionized water; the wetting agent is sodium dodecylbenzene sulfonate, and the rust inhibitor is triethanolamine.
[0031] Example 3 The difference between this embodiment and Embodiment 1 is that: An aerospace titanium alloy cutting fluid, by weight percentage, comprises the following components: 1.5% carbon quantum dot@titanium dioxide core-shell structure material, 0.5% wetting agent, 2.5% rust inhibitor, and the balance being deionized water; the wetting agent is sodium dodecylbenzene sulfonate, and the rust inhibitor is triethanolamine.
[0032] Example 4 This embodiment provides a method for preparing an aerospace titanium alloy cutting fluid, which is used to prepare the aerospace titanium alloy cutting fluid in Example 1. According to the required weight percentage of each component, carbon quantum dot@titanium dioxide core-shell structure material, wetting agent and rust inhibitor are added to deionized water. The carbon quantum dot@titanium dioxide core-shell structure material is ultrasonically treated for 25 minutes, then heated to 70°C and stirred for 25 minutes at a stirring speed of 250 rpm to obtain the aerospace titanium alloy cutting fluid with carbon quantum dot@titanium dioxide core-shell structure.
[0033] Example 5 The difference between this embodiment and Embodiment 1 is that: S1. Preparation of carbon quantum dots: By weight, 1 part of sucrose was placed in 30 parts of ethanol solution and ultrasonically treated in a cold water bath for 20 min at a temperature of 2°C. Then, 3 parts of 30% hydrogen peroxide solution were added to obtain the first mixture. The first mixture was then placed in a reaction vessel and heated to 120°C for 12 h to obtain a precipitate. The precipitate was centrifuged and washed to obtain carbon quantum dots. S2. Preparation of carbon quantum dot@titanium dioxide core-shell structure: By weight, 1 part of carbon quantum dots was dissolved in 30 parts of ethanol solution and stirred to obtain a second mixture. The size of the carbon quantum dots used was 6nm±1nm. Acetic acid solution was added dropwise while stirring until the pH of the second mixture was 1.7 and the mass concentration of the acetic acid solution was 60%. Finally, 12 parts of tetrabutyl titanate were added dropwise. After stirring and mixing at room temperature for 8 hours, a third mixture was obtained. The stirring speed was 100rpm and the room temperature was 20℃. After centrifuging and washing the third mixture, carbon quantum dot@titanium dioxide core-shell material with a size of 80~100nm was obtained.
[0034] Example 6 The difference between this embodiment and Embodiment 1 is that: S1. Preparation of carbon quantum dots: By weight, 3 parts of sucrose were placed in 50 parts of ethanol solution and ultrasonically treated in a cold water bath for 30 min at a temperature of 6°C. Then, 5 parts of 30% hydrogen peroxide solution were added to obtain the first mixture. The first mixture was then placed in a reaction vessel and heated to 200°C for 24 h to obtain a precipitate. The precipitate was centrifuged and washed to obtain carbon quantum dots. S2. Preparation of carbon quantum dot@titanium dioxide core-shell structure: By weight, 5 parts of carbon quantum dots were dissolved in 50 parts of ethanol solution and stirred to obtain a second mixture. The size of the carbon quantum dots used was 6nm±1nm. Acetic acid solution was added dropwise while stirring until the pH of the second mixture was 1.7 and the mass concentration of the acetic acid solution was 80%. Finally, 20 parts of tetrabutyl titanate were added dropwise. After stirring and mixing at room temperature for 12 hours, a third mixture was obtained. The stirring speed was 150rpm and the room temperature was 30℃. After centrifuging and washing the third mixture, carbon quantum dot@titanium dioxide core-shell material with a size of 80~100nm was obtained.
[0035] Example 7 The difference between this embodiment and embodiment 4 is that: According to the required weight percentage of each component, the carbon quantum dot@titanium dioxide core-shell structure material, wetting agent and rust inhibitor were added to deionized water. After ultrasonic treatment for 20 minutes, the mixture was heated to 60℃ and stirred for 20 minutes at a stirring speed of 200 rpm to obtain the aerospace titanium alloy cutting fluid with carbon quantum dot@titanium dioxide core-shell structure.
[0036] Example 8 The difference between this embodiment and embodiment 4 is that: Preparation of cutting fluid: According to the required weight percentage of each component, the carbon quantum dot@titanium dioxide core-shell structure material, wetting agent and rust inhibitor are added to deionized water. After ultrasonic treatment for 30 min, the mixture is heated to 80℃ and stirred for 30 min at a stirring speed of 300 rpm to obtain the aerospace titanium alloy cutting fluid with carbon quantum dot@titanium dioxide core-shell structure.
[0037] Example 9 The difference between this embodiment and Embodiment 1 is that: In step S1, sucrose is replaced with chitosan.
[0038] Example 10 The difference between this embodiment and Embodiment 1 is that: In step S1, sucrose is replaced with glucose.
[0039] Example 11 This embodiment provides an application of aerospace titanium alloy cutting fluid. Based on an aerospace titanium alloy cutting fluid in Embodiment 1, the aerospace titanium alloy cutting fluid is applied to the cutting lubrication of aerospace titanium alloys. The specific application method is as follows: each aerospace titanium alloy cutting is divided into a front section, a middle section and a rear section according to the total cutting time, wherein the time ratio of the front section, the middle section and the rear section is 3:3:4, and the cutting fluid used in each section is different. In the initial stage, the cutting fluid used is aerospace titanium alloy cutting fluid. After the aerospace titanium alloy cutting fluid is sprayed onto the titanium alloy cutting part for cooling and lubrication, the used aerospace titanium alloy cutting fluid is collected and filtered through a 0.075mm filter screen to obtain a first-time reuse cutting fluid. In the middle stage, the cutting fluid used is a primary recycled cutting fluid. The primary recycled cutting fluid is sprayed again to cool and lubricate the cutting parts of the aerospace titanium alloy. Then, the used primary recycled cutting fluid is collected and centrifuged at 75,000 rpm for 4 minutes to obtain secondary recycled cutting fluid. In the later stage, the cutting fluid used is a mixture of recycled cutting fluid and aerospace titanium alloy cutting fluid in a volume ratio of 8:3. After mixing the recycled cutting fluid and aerospace titanium alloy cutting fluid in a volume ratio of 8:3, the cutting parts of aerospace titanium alloy are cooled and lubricated again by spraying. The cutting fluid flow rate is the same at 7.5 L / min when cutting aerospace titanium alloys in the front, middle and rear sections.
[0040] Example 12 The difference between this embodiment and embodiment 11 is that: The specific application method is as follows: each cutting of aerospace titanium alloy is divided into the first stage, the middle stage and the last stage according to the total cutting time, wherein the time ratio of the first stage, the middle stage and the last stage is 3:3:4, and the cutting fluid used in each stage is different; In the initial stage, the cutting fluid used is aerospace titanium alloy cutting fluid. After the aerospace titanium alloy cutting fluid is sprayed onto the titanium alloy cutting part for cooling and lubrication, the used aerospace titanium alloy cutting fluid is collected and filtered through a 0.05mm filter screen to obtain a first-time reuse cutting fluid. In the middle stage, the cutting fluid used is a primary recycled cutting fluid. The primary recycled cutting fluid is sprayed again to cool and lubricate the cutting parts of the aerospace titanium alloy. Then, the used primary recycled cutting fluid is collected and centrifuged at 5000 rpm for 3 minutes to obtain secondary recycled cutting fluid. In the later stage, the cutting fluid used is a mixture of recycled cutting fluid and aerospace titanium alloy cutting fluid in a volume ratio of 8:3. After mixing the recycled cutting fluid and aerospace titanium alloy cutting fluid in a volume ratio of 8:3, the cutting parts of aerospace titanium alloy are cooled and lubricated again by spraying. The cutting fluid flow rate is the same at 5 L / min when cutting aerospace titanium alloys in the front, middle and rear sections.
[0041] Example 13 The difference between this embodiment and embodiment 11 is that: The specific application method is as follows: each cutting of aerospace titanium alloy is divided into the first stage, the middle stage and the last stage according to the total cutting time, wherein the time ratio of the first stage, the middle stage and the last stage is 3:3:4, and the cutting fluid used in each stage is different; In the initial stage, the cutting fluid used is aerospace titanium alloy cutting fluid. After the aerospace titanium alloy cutting fluid is sprayed onto the titanium alloy cutting part for cooling and lubrication, the used aerospace titanium alloy cutting fluid is collected and filtered through a 0.1mm filter screen to obtain a first-time reuse cutting fluid. In the middle stage, the cutting fluid used is a primary recycled cutting fluid. The primary recycled cutting fluid is sprayed again to cool and lubricate the cutting parts of the aerospace titanium alloy. Then, the used primary recycled cutting fluid is collected and centrifuged at 10,000 rpm for 5 minutes to obtain secondary recycled cutting fluid. In the later stage, the cutting fluid used is a mixture of recycled cutting fluid and aerospace titanium alloy cutting fluid in a volume ratio of 8:3. After mixing the recycled cutting fluid and aerospace titanium alloy cutting fluid in a volume ratio of 8:3, the cutting parts of aerospace titanium alloy are cooled and lubricated again by spraying. The cutting fluid flow rate is the same at 10 L / min when cutting aerospace titanium alloys in the front, middle and rear sections.
[0042] Example 14 The difference between this embodiment and Embodiment 1 is that: The carbon quantum dot@titanium dioxide core-shell structure material is a commercially available brown-black carbon quantum dot L-CQDs / TiO2 ionic liquid labeled polymer / nanomaterial from Beike.
[0043] This carbon quantum dot@titanium dioxide core-shell structure material is often used in the field of composite photocatalysts. However, its effect is not good when used in cutting fluid lubrication, and the cost is too high.
[0044] Experimental Example 1 To test the lubrication performance of the aerospace titanium alloy cutting fluid of the present invention, transmission electron microscopy (TEM) was performed on the carbon quantum dots prepared in Example 1, and TEM was also performed on the carbon quantum dot@titanium dioxide core-shell material prepared in Example 1. Figure 1 and 2 It can be seen that the carbon quantum dots and carbon quantum dot@titanium dioxide core-shell materials prepared in Example 1 of the present invention have good morphological characteristics; The aerospace titanium alloy cutting fluid prepared in Example 1 was subjected to ball-disc rotary friction experiments. The ball material was GCr15, the sample disk material was TC4, the testing machine speed was 150 rpm, and the loads were 8, 10, 12, and 15 N. The friction-reducing and lubrication performance data of the composite lubricating oil additive under different loads were obtained as follows: Figure 3 As shown.
[0045] To test the lubrication performance of this invention for titanium alloy cutting, a cutting experiment was conducted to compare the aerospace titanium alloy cutting fluid prepared in Example 1 with the titanium alloy cutting fluids prepared in Comparative Examples 1, 2, and 3. Comparative Example 1: For comparison with Example 1, Comparative Example 1 did not add carbon quantum dot@titanium dioxide core-shell structure material. The titanium alloy cutting fluid of Comparative Example 1 included, by weight percentage: 0.5% wetting agent, 1% rust inhibitor, and 98.5% water. The preparation method is as follows: 0.5% wetting agent and 1% rust inhibitor are added to water and ultrasonicated for 30 minutes. Then, the mixture is stirred for 20 minutes under heating at 60°C to obtain titanium alloy cutting fluid.
[0046] Comparative Example 2: To compare with Example 1, Comparative Example 2 replaced the carbon quantum dot@titanium dioxide core-shell structure material with carbon quantum dot material. The titanium alloy cutting fluid of Comparative Example 2, by weight percentage, included: 0.5% carbon quantum dots, 0.5% wetting agent, 1% rust inhibitor, and 98% water. The preparation method is as follows: 0.5% carbon quantum dots, 0.5% wetting agent, and 1% rust inhibitor are added to water and ultrasonicated for 30 minutes. Then, the mixture is stirred for 20 minutes under heating at 60°C to obtain carbon quantum dot titanium alloy cutting fluid.
[0047] Comparative Example 3: To compare with Example 1, Comparative Example 3 replaced the carbon quantum dot@titanium dioxide core-shell structure material with titanium dioxide material. The titanium alloy cutting fluid of Comparative Example 3, by weight percentage, included: 0.5% titanium dioxide, 0.5% wetting agent, 1% rust inhibitor, and 98% water. The preparation method is as follows: 0.5% titanium dioxide, 0.5% wetting agent, and 1% rust inhibitor are added to water and ultrasonicated for 30 minutes. Then, the mixture is stirred for 20 minutes under heating at 60°C to obtain titanium dioxide titanium alloy cutting fluid.
[0048] Experimental Example 2 Comparison of surface microstructures of titanium alloys after machining: The cut surfaces of the titanium alloys from Examples 1 and Comparative Examples 1-3 were scanned to obtain microstructure scan images, such as... Figure 4 As shown. From Figure 4 As can be seen, compared with Comparative Examples 1, 2, and 3, the cutting fluid for aerospace titanium alloys in Example 1, due to the addition of carbon quantum dots@titanium dioxide core-shell structure material, resulted in the shallowest grinding marks and better surface quality after cutting. This indicates that the cutting fluid prepared by the method of the present invention has better lubrication performance.
Claims
1. An aeronautical titanium alloy cutting fluid, characterized by, By weight percentage, it includes the following components: 0.5-1.5% carbon quantum dot@titanium dioxide core-shell structure material, 0.5% wetting agent, 1-2.5% rust inhibitor, and the balance being deionized water; The preparation method of the carbon quantum dot@titanium dioxide core-shell structure material is as follows: S1. Preparation of carbon quantum dots: By weight, 1-3 parts of sucrose, chitosan, or glucose are placed in 30-50 parts of ethanol solution and ultrasonically treated in a cold water bath for 20-30 minutes. Then, 3-5 parts of 30% hydrogen peroxide solution are added to obtain the first mixture. The first mixture is then placed in a reaction vessel and heated to 120-200℃ for 12-24 hours to obtain a precipitate. After centrifugation and washing, carbon quantum dots are obtained. S2. Preparation of carbon quantum dot@titanium dioxide core-shell structure: By weight, 1-5 parts of carbon quantum dots are dissolved in 30-50 parts of ethanol solution and stirred to obtain a second mixture. While stirring, acetic acid solution is added dropwise until the pH of the second mixture is 1.
7. Finally, 12-20 parts of tetrabutyl titanate are added dropwise. After stirring and mixing at room temperature for 8-12 hours, a third mixture is obtained. After centrifuging and washing the third mixture, carbon quantum dot@titanium dioxide core-shell material is obtained.
2. The cutting fluid for titanium alloy of claim 1, wherein The wetting agent is sodium dodecylbenzenesulfonate, and the rust inhibitor is triethanolamine.
3. The cutting fluid for titanium alloy of claim 1, wherein In step S1, the temperature of the cold water bath is 2~6℃.
4. The cutting fluid for titanium alloy of claim 1, wherein The mass concentration of the ethanol solution in step S1 and the ethanol solution in step S2 is 95%, and the mass concentration of the acetic acid solution in step S2 is 60-80%.
5. The cutting fluid for titanium alloy of claim 1, wherein The stirring speed in step S2 is 100~150 rpm, and the room temperature is 20~30℃.
6. The cutting fluid for titanium alloy of claim 1, wherein In step S2, the carbon quantum dots used are 6nm ± 1nm in size.
7. A method for preparing an aeronautical titanium alloy cutting fluid, for preparing an aeronautical titanium alloy cutting fluid as claimed in claim 1, characterized in that: According to the specified ratio, carbon quantum dot@titanium dioxide core-shell structure material, wetting agent and rust inhibitor are added to deionized water, ultrasonically treated for 20-30 minutes, heated to 60-80℃, and stirred for 20-30 minutes. The stirring speed is 200-300 rpm, thus obtaining the aerospace titanium alloy cutting fluid.
8. Use of an aerospace titanium alloy cutting fluid based on the aerospace titanium alloy cutting fluid according to claim 1, characterized in that, The aforementioned aerospace titanium alloy cutting fluid is applied to the cutting and lubrication of aerospace titanium alloys.
9. The application of the aerospace titanium alloy cutting fluid according to claim 8, characterized in that, The application method is as follows: Each cutting of aerospace titanium alloy is divided into three stages according to the total cutting time: the first stage, the middle stage, and the last stage. The time ratio of the first stage, the middle stage, and the last stage is 3:3:
4. In the initial stage, the aerospace titanium alloy cutting fluid is sprayed onto the titanium alloy cutting part for cooling and lubrication. The used aerospace titanium alloy cutting fluid is then collected and filtered through a 0.05~0.1mm filter screen to obtain a first-use reusable cutting fluid. In the middle stage, the primary recycled cutting fluid is sprayed again to cool and lubricate the cutting part of the aerospace titanium alloy. Then, the used primary recycled cutting fluid is collected and centrifuged at a speed of 5000~10000 rpm for 3~5 minutes to obtain secondary recycled cutting fluid. In the later stage, the secondary recycled cutting fluid and the aerospace titanium alloy cutting fluid are mixed at a volume ratio of 8:3, and the cutting parts of the aerospace titanium alloy are cooled and lubricated again by spraying. The cutting fluid flow rate is the same when cutting aerospace titanium alloys in the front, middle and rear sections, which is 5~10L / min.
Citation Information
Patent Citations
Preparation method of carbon quantum dot / titanium dioxide nano composite material
CN110180521A
Titanium alloy rolling lubricating liquid based on core-shell structure SiO2 (at) Graphene quantum dots and preparation method thereof
CN112920876A
